2010
DOI: 10.1177/1721727x1000800107
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Ifn-Gamma Release Assays in Clinical Management of Difficult TB Cases: Evidence from Clinical Practice

Abstract: Performance of T-SPOT.TBTM (TS-TB) and QuantiFERON TB Gold-In tube (QFT-IT) assays was evaluated for detection of M. tuberculosis (Mtb) infection in patients with suspected extra-pulmonary or smear-negative pulmonary tuberculosis (TB) in a low prevalence country. Twenty-one out of 35 patients were affected by active TB. Mtb culture isolation was achieved in 76% of cases. Tuberculin skin testing (TST), TS-TB, and QFT-IT yielded a positive result in 67%, 95% and 81% of cases, respectively. Agreement of interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The effect on plaque stability is explained by the observation that blockade of IL-12 may diminish the recruitment ofT cells into the plaque (80)(81)(82)(83).…”
Section: Interleukin-/8mentioning
confidence: 99%
“…The effect on plaque stability is explained by the observation that blockade of IL-12 may diminish the recruitment ofT cells into the plaque (80)(81)(82)(83).…”
Section: Interleukin-/8mentioning
confidence: 99%
“…Cellular-mediated and humoral-mediated responses are affected in general psychiatry traumatic disorders, as is the production of cytokines (13)(14)(15). The hypothalamic-pituitaryadrenal axis responds to several compounds, such as inflammatory cytokines: tumor necrosis factor (TNF)-u, interleukin-I (lL-I) alpha and beta, interleukin-18, interleukin-33 and interleukin-6 (16)(17)(18)(19)(20)(21)(22). Several studies proved the correlation between stress and progression of various types of cancer and cancer recurrence, in humans (23)(24)(25).…”
mentioning
confidence: 99%
“…CD40L as well as IL-I produced by T cells induce macrophages to release interstitial collagenases, including MMP-I, -8, and -13 (14-17). The shoulder region of plaques as well as areas of foam cell accumulation contain MMP-9, a member of the gelatinase class of the rnetalloproteinase family (18)(19)(20)(21)(22). Human plaque analysis has revealed that MMP-9 is catalytically active and may thus contribute to the dysregulation of extracellular matrix that leads to plaque rupture during the complication of atherothrombosis (23)(24)(25)(26).…”
Section: Genesis Of Atherosclerosismentioning
confidence: 99%